Clinical Perspectives, Surgical Approach, Outcome and Limitations of External Dacryocystorhinostomy - Marappan , Harikrishnan (Medical Research and Its Applications Vol. 5, 2024)
External dacryocystorhinostomy (DCR) is a surgical procedure aimed at restoring the drainage pathway of tears in patients suffering from nasolacrimal duct obstruction. This chapter provides an in-depth exploration of the surgical technique, indications, clinical outcomes, postoperative care and limitations associated with external DCR.